2005
DOI: 10.1128/aem.71.6.3126-3130.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Islands in theCorynebacterium efficiensGenome

Abstract: Corynebacterium efficiens is a gram-positive nonpathogenic bacterium which can grow and produce glutamate at 40°C or above. By using the cumulative GC profile method, we have identified four genomic islands which have many unifying genomic island-specific features in the C. efficiens genome. The presence of the gene encoding an aspartate kinase in a genomic island helps explain the unexpected low thermal stability of this enzyme; i.e., the adaptive mutations have not occurred extensively due to the recent hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Previous work indicated that genomic island contains cluster of horizontally transferred genes (Zhang and Zhang, 2005). In present study, five genomic islands were detected in the genome of S. pomeroyi DSS-3 (Fig.…”
Section: Evolutionary Analysis and General Conclusionmentioning
confidence: 55%
“…Previous work indicated that genomic island contains cluster of horizontally transferred genes (Zhang and Zhang, 2005). In present study, five genomic islands were detected in the genome of S. pomeroyi DSS-3 (Fig.…”
Section: Evolutionary Analysis and General Conclusionmentioning
confidence: 55%
“…Moreover, none was found in PcaCP, PaeCP and CphCP. When looking at integrase and transposase encoding sequences, we found that DaCP sequence is very close (b 1000 bp) to a transposase and an integrase, and is preceded by a tRNA synthetase, commonly found next to transposable elements (Klockgether et al, 2004;Zhang and Zhang, 2005). Inverted repeats were also detected, suggesting that CP can be transmitted also through transposition.…”
Section: Lateral Gene Transfer Among Prokaryotesmentioning
confidence: 91%
“…Both genomic islands are flanked at one end by ISs. Genomic island CEGI-3 (40.4 kb) is flanked by a 26-bp direct repeat element and encodes an integrase at the 5Ј junction (494). Seven of the 50 predicted genes of CEGI-3 encode proteins similar to late proteins of the lytic bacteriophage BFK20 (52).…”
Section: Prophage-like Elements In the C Glutamicum Genomementioning
confidence: 99%